Educação do campo: o SOME como uma política de formação no campo - TRINDADE, Maria Eliene Trindade da (2021)
This article has as its object of study the Rural Education policy in particular, the Modular High School in the Field, the production takes place in the context of Vila Guarumã in the municipality of Acará located 18 km away from the municipal headquarters; studies the Modular Teaching Organization System (SOME). A qualitative research was conducted using semi-structured questionnaires and interviews with open dialogues with teachers and students enrolled in the modular system for data collection. The emergence of SOME was due to the need to expand Brazilian basic education aiming at a training policy for young people and adults from the countryside who have the desire to achieve a qualification through high school. This paper aims to discuss the contribution of SOME to Rural Education in the reflection of educational policy in the formation of rural students. Focusing on the process of formation from SOME, we ask: how or not SOME contributes to the formation of rural education and does it respond to the training needs of rural youth? Given this, I present as a result the challenges faced by students and teachers new to SOME; the contribution of Modular Education in Guarumã village and the important role of SOME in the social inclusion of rural students through Rural Education.